Pola Rekrutmen, Mortalitas, dan Laju Eksploitasi Ikan Lemuru (Amblygaster sirm, Walbaum 1792) di Perairan Selat Sunda - Nidya KARTINI; Mennofatria BOER; Ridwan AFFANDI (Universitas Jambi, 2017)
Sunda Strait has high potential of pelagic fish resources, one of which is spotted sardinella (Amblygaster sirm). High market demand of spotted sardinella leads to its high exploitation. Management of sustainable used of this species need various biological information of the target species.The aims of this research wereto analyze of therecruitment pattern, mortality, and exploitation rate of spotted sardinella. Sampling was conducted in April to August 2015 from the catchment landed at Labuan Coastal Fishing Port, Banten. Fish samples taken during the study consisted of Â 527 males and 245 females. The results showed thatpeak recruitment season for spotted sardinella occurs in Maret (11.64%) and July (13.67%).The natural mortality (M), fishing mortality (F), total mortality (Z) for male were 0,33; 5,30; 5,63 year-1 respectively, and for female were 0,51; 7,75;8,27 year-1 respectively. Exploitation rate (E) for male was 0,94 year-1 and for female was 0,93 year-1.Keywords : exploitation, growth, mortality, spotted sardinella, Sunda Strait